A novel bispecific aptamer targeting LAG3 and HER2 enhances T cell-mediated immunotherapy against HER2-positive cancer cells - Guo, Rui; Chen, Xiaoyang; Ying, Lu; Zhang, Wenjing; Sabeel, Zufa; Zhao, Lianhui; Dong, Jian; Dong, Yiyang; Yang, Zhao (Frontiers in Immunology, 2025)
ObjectiveMalignant tumors are one of the leading causes of human death worldwide. In recent years, immunotherapy has become an emerging treatment method following surgery, radiotherapy, and chemotherapy. The study focused on two critical targets: human epidermal growth factor receptor 2 (HER2), a well-established tumor biomarker overexpressed in malignancies such as non-small cell lung cancer and hepatocellular carcinoma, and lymphocyte activation gene 3 (LAG3), an immune checkpoint molecule predominantly expressed on activated T lymphocytes and natural killer cells. Herein, we developed a novel bispecific aptamer (HLB-apt) to investigate its dual-targeting therapeutic potential in regulating tumor-immune cell interactions.MethodFirstly, the Moe algorithm was used to simulate the docking results between the aptamer and the corresponding protein. Then, the constructed HLB-apt was validated. In addition, based on A549, HepG2 cells and Jurkat cells, the functions and mechanisms of HLB-apt acting simultaneously with A549, HepG2 cells and Jurkat cells were verified through in vivo and in vitro experiments.ResultsHLB-apt demonstrated specific binding capacity to both HER2-expressing tumor cells (A549 and HepG2) and LAG3-positive Jurkat cells. Notably, HLB-apt enhanced the killing effect of Jurkat cells on A549 and HepG2 cancer cells, with a killing rate of up to 29.00% for A549 and 7.46% for HepG2. Mechanistically, HLB-apt promotes the expression and secretion of IL-2, TNF-α, and granzyme B in activated Jurkat cells, and increases the expression of BAK1, BIM, and BAX in A549 and HepG2 cells. More importantly, HLB-apt significantly inhibited tumor growth in A549 and HepG2 tumor bearing mice and H&E staining revealed no overt histopathological abnormalities in major organs.ConclusionOur findings demonstrate that HLB-apt exerts dual antitumor effects likely through simultaneously targeting LAG3 on T cells and HER2 on tumor cells, facilitating T cell recruitment and potentially interfering with immune checkpoint pathways. Therapeutic efficacy was markedly enhanced in tumor-bearing mice receiving combined HLB-apt and Jurkat cell administration, This HLB-apt holds promising clinical potential for malignancies characterized by HER2 overexpression.